Pré-tratamento organossolve do bagaço de cana-de-açúcar para a produção de etanol e obtenção de xilooligômeros - Wolf, Lucia Daniela (Universidade Federal de São Carlos, 2011)
Sugarcane bagasse is an abundant lignocelulosic byproduct, due to the high ethanol production from sugarcane juice, which turns this residue an attractive alternative for obtaining cellulosic ethanol and other products of higher value added. However, the use of bagasse requires a pre-treatment step for better use of its fractions. It was proposed in this study, an evaluation of different operational conditions of bagasse Organsolv pre-treatment, followed or not by alkaline delignification, acid catalyzed or not, aiming the application of cellulose to ethanol production and xylan to produce xylo-oligosaccharides (XO). The pretreatment reactions were conducted in a high pressure reactor (Parr) under different temperature conditions (150, 170 and 190°C), time (10, 30, 60 and 90min), ethanol concentration (30, 50 and 70%), with solid:liquid ratio of 1:10 (w/v) and stirring speed of 300 rpm. The pre-treatments with higher severity factor were followed by delignification with 1% NaOH (w/v) at 100°C for 1 hour. Acid catalysis with 1% H2SO4 (w/w) was used in the pretreatment condition at 190°C/10min/50%ethanol with or without the alkaline delignification step. The evaluation of pre-treatment efficiency was carried out using structural, chemical and gravimetric characterization of the obtained solid fraction, cellulose enzymatic conversion in the hydrolysis of this fraction and ethanol yield after hydrolisate fermentation. The liquid fraction was characterized with respect to its xylan yield and the ratio obtained between xylan oligomers and xylose. The conditions of higher severity factor presented higher lignin and hemicelulose solubilization with average values of 80% and 86,3%, respectively, and average cellulose degradation of 2,4%. The same conditions, when associated with alkaline delignification, led to a increase on lignin and hemicelulose solubilization, 89,7% and 96,8%, respectively. However, the average initial cellulosic fraction loss of 14% was depicted. The use of acid catalyst, despite having promoted increase in solubilization of lignin (4%) and hemicelulose (12%), led to a expressive degradation of the cellulosic fraction, with mass loss of 34% and 12,6%, with and without alkaline delignification, respectively. The pre-treatment condition at 190°C/10min/50%ethanol promoted a higher enzymatic conversion (61,2%) with cellulose degradation of only 1% and after alkaline delignification step, reached 88,2%. The alkaline delignification led to a conversion increase for all the conditions tested, but also led to significant cellulose losses. On the other hand, the use of the acid catalyst had no significant effect on enzymatic hydrolysis. The fermentation of the hydrolisates was equally satisfactory for all the conditions evaluated, with average yield of 80%. The SEM analysis showed changes on the morphological structure of the fiber compared to the in natura bagasse, for the different pre-treatment conditions. The black liquor obtained after the pretreatment was evaluated with respect to its hemicelulosic fraction, obtaining 54,5% of xylooligomers and only 2% of xylose at the best condition (170°C/60min/50%ethanol), with 75% of recovery yield of xylan initially present in the bagasse.
Keywords: Deslignificação; Hidrólise enzimática; Alcool; Xilooligossacarídeos; Bagaço de cana-de-açúcar; Pré- tratamento organossolve; Deslignificação alcalina; Sugarcane bagasse; Organosolv pre-tretament; Alkaline delignification; Enzymatic Hydrolysis; Ethanol; ENGENHARIAS::ENGENHARIA QUIMICA